GOOD GOVERNANCE DAN REFORMASI BIROKRASI DI INDONESIA - R Siti Zuhro (Pusat Penelitian Politik, 2010)
With the downfall ofSoeharto s New Order regime the authoritarian nature of the bureaucratic system wasexposed The implementation ofnew political laws since 1999 gave rise to an invigorated roleforpoliticalpartiesand the implementation ofa government regulationfor a neutral bureaucracy resulted in its declining involvementin politics A strongparliament and the increasingpolitical awareness ofbureaucrats have become a reality todayThese changes have put paid to questions about the involvement ofpolitical parties and the influence of societalforces in theformation ofpolicy The bureaucracy can no longer exist as it was in the New Order and infact hasresponded to societal needs by adjusting to the new political climate Indonesian politics under the transition eratakes on a wider significancefor one ofthe main results has been the emergence ofbureaucraticpluralism a morepluralistic political system that is more open to the influence ofthese societalforces Improvement in governancebecame possible however with the rise of the reformation since 1998 At this time the debate on governance inIndonesia began with a consideration of good governance The post Soeharto era was seen by reformists as along awaited opportunity to improve government policy so that people would not only follow the government sdecisions but would also contribute to the decision making process Indonesian demanded more democraticgovernance that is more regular interaction between government and civil society andfreerparticipation by thelatter in government institutionsKeywords Governance policy democratization reformation good governance